Targeting cytokine signaling checkpoint CIS activates NK cells to protect from tumor initiation and metastasis. (1st February 2017) - Putz, Eva M.; Guillerey, Camille; Kos, Kevin; Stannard, Kimberley; Miles, Kim; Delconte, Rebecca B.; Takeda, Kazuyoshi; Nicholson, Sandra E.; Huntington, Nicholas D.; Smyth, Mark J.
ABSTRACT: The cytokine-induced SH2-containing protein CIS belongs to the suppressor of cytokine signaling (SOCS) protein family. Here, we show the critical role of CIS in suppressing natural killer (NK) cell control of tumor initiation and metastasis. Cish -deficient mice were highly resistant to methylcholanthrene-induced sarcoma formation and protected from lung metastasis of B16F10 melanoma and RM-1 prostate carcinoma cells. In contrast, the growth of primary subcutaneous tumors, including those expressing the foreign antigen OVA, was unchanged in Cish -deficient mice. The combination of Cish deficiency and relevant targeted and immuno-therapies such as combined BRAF and MEK inhibitors, immune checkpoint blockade antibodies, IL-2 and type I interferon revealed further improved control of metastasis. The data clearly indicate that targeting CIS promotes NK cell antitumor functions and CIS holds great promise as a novel target in NK cell immunotherapy.